Lower limb performance in anterior cruciate ligament reconstructed individuals - Flanagan, E. P.; Harrison, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This experiment examined lower limb performance in individuals with previous history of anterior cruciate ligament rupture and reconstruction. 10 volunteers took part in the study. Lower limb performance was assessed with maximal effort countermovement, drop and rebound jumps on a force sledge apparatus. The subjects' contra-lateral, uninjured leg was used as an internal control. No significant differences were observed in any of the measured variables, in any of the jumping procedures between the involved and uninvolved leg. This suggests that current reconstructive practices and post-surgery rehabilitation techniques may have the ability to restore ACL deficient legs to a similar level of performance to an uninvolved control leg in dynamic, non-fatiguing, maximal effort jumping activity.